Internet of Thing Implementation in The Library System (A Case Study of STMIK Bina Bangsa Kendari) - Aris, Faizal; Kasau, Sukirno (Journal of INISTA, 2025)
The subject of this article is the Internet of Things (IoT), particularly in the context of libraries. The author explains the definitions and concepts of IoT, the importance of IoT in libraries, and the potential applications of IoT for libraries. This research is located at the STMIK Bina Bangsa Kendari campus. The goal of this research is to design and simulate a prototype of an IoT-based library system utilizing UHF RFID technology. The research method used in this study is the development of a research and development model. The design of the intelligent library system development is based on two components: system hardware architecture and software development. The development approach uses a prototype development model. The library system can monitor the condition of books in real-time, whether they are available on the shelves, loaned out, or not on the shelves. The library system can provide information in the form of shelf monitoring if a book is misplaced on the shelf. The use of UHF RFID technology allows the application to read tag labels up to a maximum distance of 6 meters, while to support optimal QR Code reading in a room measuring 4 x 4 x3 meters (L x W x H), a minimum of one bulb with a power of 18 watts is required.